2018
DOI: 10.15386/cjmed-931
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings during follow-up scans in oncological patients

Abstract: Background and aimTo assess the prevalence of incidental findings during follow-up scans of patients with oncologic pathology.Methods499 follow-up scans from different patients with cancer pathology were retrospectively analyzed. Findings which were not suspected by the clinician or known from previous scans were considered as incidental lesions. We excluded lesions that were already suspected by the clinician or were already recorded in the patient’s history before the initial computed tomography (CT) scan. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Indeed, cancer patients may have progressive cancer-or cancer-treatment related lung abnormalities, which may be complicated to interpret if the patient becomes symptomatic. Moreover, the rate of incidental findings in cancer patients may be relatively high: a study of 510 patients reported incidental findings in up to 28% of patients, including 3.4% of patients with a significant finding that either changed the cancer therapy or required immediate treatment (34).…”
Section: Optimizing Medical Imaging In Radiotherapy During the Covid-mentioning
confidence: 99%
“…Indeed, cancer patients may have progressive cancer-or cancer-treatment related lung abnormalities, which may be complicated to interpret if the patient becomes symptomatic. Moreover, the rate of incidental findings in cancer patients may be relatively high: a study of 510 patients reported incidental findings in up to 28% of patients, including 3.4% of patients with a significant finding that either changed the cancer therapy or required immediate treatment (34).…”
Section: Optimizing Medical Imaging In Radiotherapy During the Covid-mentioning
confidence: 99%